Kenya, into the second decade : report of a mission sent to Kenya by the World Bank - Burrows, John R. (Baltimore : Published for the World Bank by the Johns Hopkins University Press, 1975)
his examines Kenya's exceptional achievements since gaining independance, it looks at the massive problems that are yet to be overcome
Includes bibliography (p. 76-80) and index.
eng
Keywords: Agricultural development -- Kenya; Capital formation -- Kenya; Economic history -- Kenya; Economic planning; Economic policy